Cryopreservation of Excised Embryos of Rambutan (Nephelium Lappaceum L.) Using Vitrification Technique - Camillus Ginibun, Florence (2001)
The present study evaluates the effects of various loading solutions, concentrations of glycerol and vitrification solutions and their time of exposure on the vitrification of rambutan embryos in liquid nitrogen. In the initial study to evaluate the effects of loading solutions on survival, excised embryos were exposed to four loading solutions. The two most promising loading solutions were LB (1.5 M glycerol + 0.4 M sucrose + 5% DMSO), which gave 44.0 % viability and 32.4 % survival and LA (2.0 M glycerol + 0.4 M sucrose) which gave 39.3 % viability and 28.1 % survival after freezing. The effects of different concentrations of glycerol (0 - 2.0 M) in the most promising loading solutions were evaluated further. For loading solution LB, 1.5 M glycerol gave highest survival of 22.7 %. For loading solution LS, 1.5 M glycerol gave highest survival of 22.7 %. For loading solution LA, 0 M glycerol or the use of only 0.4 M sucrose gave the highest viability of 76.0 % and survival of 59.0 %. Hence, loading solution with only 0.4 M sucrose (LA without glycerol) was established in this study as the most effective loading solution for rambutan embryos. The effects of exposure time (0-16 hours) to the best loading solution on survival of rambutan embryos were further investigated. It was found that 8 hours duration gave the highest viability (47.7 %) and survival (32.8 %). Having confirmed the best loading treatment, the study further evaluates the effects of six vitrification solutions on survival of rambutan embryos in liquid nitrogen. The results show that after freezing, L Solution gave the highest viability (46.0 %) and survival (24.0 %). L Solution was therefore selected as the most effective vitrification solution. In optimizing the time of exposure, excised rambutan embryos were exposed to L Solution for 0 to 90 minutes before LN exposure. The highest viability (55.6 %) and survival (40.3 %) after vitirification were achieved at 60 minutes exposure. Longer exposure to L Solution for up to 90 minutes reduced survival to 16.0 %.